Evaluación de la calidad de compost a base de jacinto de agua (Eichhornia crassipes) mediante la inoculación de Trichoderma sp.” - Garrido Tipán, Mayra Karina (2016)
The present essay was performed in Guamaní, South of Quito-Ecuador, with the objective of evaluate the quality of compost-based on Water Hyacinth (Eichhornia crassipes) through the inoculation of Trichoderma sp., for which the lake San Pablo Commune Camuendo was chosen as sampling place, it possess physicochemical characteristics of water and soil propitious to the development of aquatic macrophytes, these samples were sent to the UPS laboratories in Quito and Cayambe for their analysis. Once collected the plant and the fungus isolated for composting, plants were stung into pieces of 1-3cm in diameter and compost piles were formed with an experimental design of randomized complete block design (RCBD) with 4 treatments and 4 repetitions. Trichoderma sp., was inoculated into three different doses 5 mL, 10 mL and 15 mL. The management of the essay included: 2 weekly turned and control variables: pH, temperature, moisture and electrical conductivity (EC). At the ending of the essay it was determined that T3 (15 mL) treatment showed a higher mineralization of organic matter (50.12%) and macronutrients like (P), (K), (Ca) and (Mg) increased their final concentration in more assimilable forms, parameters such as the C/N (33.84-40.00) shows Trichoderma sp. it does not contribute as expected in accelerating degradation of lignocellulosic material. The final product obtained showed structural and organoleptic quality characteristics similar to composting: dark brown color, lightweight, easily divisible and odor similar to soil, constituting an amendment to the soil.